Urochloa decumbens grown with different Eucalyptus clones in an integrated crop-livestock-forest system (Revista Ciência Agronômica, 2018)
The objective of this study is to evaluate the forage mass, chemical composition, mineral content, and mineralabsorption in signal grass (Urochloa decumbens) grown with different eucalypt clones in an integrated crop-livestock-forest(iCLF) system. The split-split-plot scheme included three replicates arranged in a completely randomized block design. Theeucalyptus clones GG 100 and I 144 (Eucalyptus grandis ´ Eucalyptus urophylla) and VM 58 (Eucalyptus grandis ´ Eucalyptuscamaldulensis) were distributed in the plots. The split plots corresponded to the growth ages of signal grass (10, 17, 24, 31,38, 45, and 52 days after corn harvest for silage). The split-split plots corresponded to two sampling sites: center of the interrow and soil under the Eucalyptus canopy. The Eucalyptus clones did not affect the forage mass of the grass. Forage mass wasincreased linearly as the grass matured and was more readily available in the center of the inter-row than under the tree canopy.The grass grown with clone I 144 presented better chemical composition, with higher levels of crude protein and phosphorusand lower levels of neutral detergent fiber. The Eucalyptus clones did not significantly affect mineral absorption. However, theEucalyptus clones, grass age, and sampling sites significantly changed potassium absorption. It is concluded that the foragemass of signal grass is suitable for use in grazing at 38 to 52 days after corn harvest in the iCLF system in the autumn seasonin the Midwest region of Minas Gerais, without compromising the chemical composition of the grass.